TEST OF EFFECTIVENESS OF RUBBER CASSAVA ROOT BARK (Manihot glaziovii) AS A SUBSTITUTE FOR SAPONINS IN AQUACULTURE - Aulia, Deni; Putra, Angkasa; Aini, Sarifah; Sabariyah, Nunung; Harahap, Kurnia Sada (Politeknik Kelautan dan Perikanan Dumai, 2023)
Rubber cassava root (Manihot glaziovii) bark contains an active substance known as Hydrogen Cyanide (HCN), which is toxic to red-blooded animals. This bark is abundant and readily available in the community’s surroundings. Therefore, this research aims to investigate the effect of using rubber cassava root bark at specific doses in eradicating red-blooded fish. The test animals used are Nile tilapia (Oreochromis niloticus). Each treatment is repeated three times and assigned specific codes: code A as a control with the application of 20 ppm saponin, and codes B, C, and D with the application of rubber cassava root bark liquid at 20 ppm, 40 ppm, and 100 ppm, respectively. The parameter used as the observation criterion is the mortality rate of the test animals over 6 hours with varying doses of rubber cassava root bark liquid. Based on the research results, it can be concluded that rubber cassava root bark liquid can be used as an alternative to replace saponin at 100 ppm. Further research is required to determine the most effective dose of rubber cassava root bark as a substitute for saponin in aquaculture.